Peer-to-Peer Systems III Third International Workshop, IPTPS 2004, La Jolla, CA, USA, February 26-27, 2004, Revised Selected Papers - Voelker, Geoffrey M.; Shenker, Scott (Theoretical Computer Science and General Issues,, 2005)
On February 26-27, 2004, the 3rd International Workshop on Peer-to-Peer S- tems (IPTPS 2004) brought researchers and practitioners together to discuss the latest developments in peer-to-peer technologies, applications, and systems. As the third workshop in the series, IPTPS 2004 continued the success of the previous workshops in pioneering the state of the art in peer-to-peer systems and identifying key research challenges in the area. The workshop received 145 submissions in the form of ?ve-page position papers. As with previous workshops, submissions went through two rounds of reviews by an international program committee of 14 experts from industry and academia.In the ?rst round eachsubmission receivedtwo reviews.In the second round we focused our attention on submissions with either positive reviews, or with reviews that expressed substantially di?erent opinions. In addition to the technical merit, the reviewing process emphasized originality and the potential of the submission to lead to interesting discussions during the workshop. Intheend,theprogramcommitteeselectedaworkshopprogramof27papers coveringawiderangeoftopicsincludingnewpeer-to-peerapplications,advances in routing, load balancing, searching, as well as transport, mobility, and other networking topics. Authors revised accepted position papers to six pages for the workshop program, and made a ?nal round of revision for this volume. The workshop was composed of eight sessions that spanned two days. To focus discussions, attendance was limited to 67 participants and included s- stantialtimeforinteractionanddiscussionbetweensessionsandatsocialevents.